Termometer dengan Keluaran Suara Berbasis Mikrokontroler ATmega8535 untuk Mengukur Suhu Ruang - Misto, Misto (Jurnal Fisika FLUX, 2009)
A thermometer with sound output has been developed. The systemconsists of a temperature sensor, a microcontroller, a voice device, and aspeaker. The temperature sensor of DS18S20 will convert the temperature todigital data. The is feed to ATmega8535 microcontroller. On the otherhand, intwelve memory of voice deviceISD2590 is recorded some numerical sound signalfrom zero to nine and word of temperature unit. For reproducing the sound signalthe data from microcontroller will switch on the memory according to itâstemperature quantity. The sound electronic signal is linked to the speaker toproduce sound. The temperature is designed to operate from 24 to 350C.